High-Dose Simvastatin for Aneurysmal Subarachnoid Hemorrhage. Issue 2 (February 2015) - Wong, George K.C.; Chan, David Y.C.; Siu, Deyond Y.W.; Zee, Benny C.Y.; Poon, Wai S.; Chan, Matthew T.V.; Gin, Tony; Leung, Michael; Zhu, X.L.; Liang, M.; Tan, H.B.; Lee, M.W.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Experimental evidence has indicated the benefits of simvastatin for the treatment of subarachnoid hemorrhage. Two randomized placebo-controlled pilot trials that used the highest clinically approved dose of simvastatin (80 mg daily) gave positive results despite the fact that a lower dose of simvastatin (40 mg daily) did not improve clinical outcomes. We hypothesized that a high dose of 80 mg of simvastatin daily for 3 weeks would reduce the incidence of delayed ischemic deficits after subarachnoid hemorrhage compared with a lower dose (40 mg of simvastatin daily) and lead to improved clinical outcomes. Methods— The study design was a randomized controlled double-blinded clinical trial. Patients with aneurysmal subarachnoid hemorrhage (presenting within 96 hours of the ictus) from 6 neurosurgical centers were recruited for 3 years. The primary outcome measure was the presence of delayed ischemic deficits, and secondary outcome measures included a modified Rankin disability score at 3 months and an analysis of cost-effectiveness. Results— No difference was observed between the groups treated with the higher dose or the lower dose of simvastatin in the incidence of delayed ischemic deficits (27% versus 24%; odds ratio, 1.2; 95% confidence interval, 0.7–2.0; P=0.586) or in the rate of favorable outcomes (modified Rankin Scale score, 0–2) at 3 months (73% versus 72%; odds ratio, 1.1; 95% confidence interval, 0.6–1.9; P=0.770). Conclusions— High-dose simvastatin treatment should not be prescribed routinely for aneurysmal subarachnoid hemorrhage. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01077206.